Development of microlearning media science concepts in senior high school: Emphasis on technology literacy - Marlina, Reni; Hamdani, Hamdani; Pamungkas, Rahmania (Jurnal Inovasi Teknologi Pendidikan, 2026)
Science learning in secondary schools often struggles to explain abstract concepts such as biological mechanisms and cellular processes, which are difficult for students to visualise using conventional teaching methods. This condition contributes to low conceptual understanding and limited technological literacy among students. To address this issue, this study developed science microlearning media designed in short, interactive, and focused learning units. This study aimed to identify the characteristics of science learning in secondary schools, determine the validity of the developed microlearning media, and examine their effectiveness in improving students’ conceptual understanding and technological literacy. The study employed a research-and-development method that included needs analysis, product development, expert validation, and feasibility testing. The validation results showed that the developed media achieved a very high validity score, with a content score of 4.52. Feasibility assessments also demonstrated high acceptance with average scores of 4.47 and 4.51, respectively. These findings indicate that the developed microlearning media are feasible and have strong potential to support science learning, particularly in facilitating students’ understanding of abstract concepts. Future studies are recommended to conduct broader experimental investigations and integrate advanced technologies to enhance the scalability and effectiveness of microlearning media.